2014
DOI: 10.5152/iao.2014.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Skin Scars Following Cochlear Implant Surgery

Abstract: OBJECTIVE:The understanding of speech is the most important outcome parameter after cochlear implantation. However, due to the excellent functional results of cochlear implantation in most patients, there is recently also a growing focus on patient comfort issues, e.g., aesthetic results. MATERIALS and METHODS:This study evaluated 34 skin scars after cochlear implant surgery in adults using the Stony Brook Scar Evaluation Scale, a well-validated instrument with a high interrater reliability and construct valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(11 reference statements)
0
2
0
1
Order By: Relevance
“…Postaural incisions are well established in middle ear surgery and are used as an approach to combined approach tympanoplasty and cortical mastoidectomy. Due to the cosmetic advantage from their concealed position and direct access to the mastoid air cells, they also play an increasing role in cochlear implant surgery [ 1 , 2 ]. They are also used in other fields of head and neck surgery, including resection of benign parotid gland tumours [ 3 ] and robotic-assisted neck dissection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postaural incisions are well established in middle ear surgery and are used as an approach to combined approach tympanoplasty and cortical mastoidectomy. Due to the cosmetic advantage from their concealed position and direct access to the mastoid air cells, they also play an increasing role in cochlear implant surgery [ 1 , 2 ]. They are also used in other fields of head and neck surgery, including resection of benign parotid gland tumours [ 3 ] and robotic-assisted neck dissection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cosmetic outcomes have also been investigated. Retroauricular skin scars had an excellent aesthetic outcome in cochlear implant surgery [ 2 ]; and in a small follow up study, Hong et al [ 9 ] noted that in 19 children a postauricular approach did not significantly affect pinna position. Shekhar and Bhavana [ 10 ] concluded that “behind the groove” incisions are better at preserving the conchomastoid angle than “in the groove” incisions and therefore give a better overall cosmetic result.…”
Section: Introductionmentioning
confidence: 99%
“…Existem trabalhos na literatura que avaliam o resultado estético da ferida operatória na cicatriz retroauricular para a cirurgia de implante coclear, utilizando a SBSES, sem validação para a língua portuguesa 60 . Uma das escalas que é validada para o português e utilizada para a avaliação de cicatrizes causadas por queimadura é a escala de Vancouver, mas esta também só avalia a percepção do examinador, sem considerar a do paciente 61 .…”
Section: Medida Da Satisfação Pós-operatória Com a Ferida Cirúrgicaunclassified